(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
The study analyses the impact of workers’ motivation on the work environment of public organizations compared to private organiza[1]tions in the city of Santa Rosa. The importance of human resources in an organization makes studying individuals’ motivation to carry out their work a very relevant field of study. Thus, this paper constitutes a great source of information for ma[1]nagers and executives who have special insights on the functiong of the company to improve decision-making, job satisfaction and organizational commitment based on the employees’ observed expectations. Moreover, addressing these concepts from a comparative perspective introduces a particularly broad and comprehensive look at the matter. The present research consisted of a mixed-methods approach with quali[1]tative and quantitative data from online literature reviews, field observa[1]tions, interviews, and surveys.